The influence of the directive in legitimizing passive in criminal proceedings the insurer: risks of liability compulsory subscription (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this article, impact of the Directive 2005/14/EC of the European Parliament and of the Council of 11 May 2005 (hereinafter referred to as the “Fifth Directive”) on the capacity of the primary coverage liability risk insurer to be made a defendant in a criminal procedure is analyzed. It is possible to differentiate, in legal terms of criminal scope, between primaryliability insurers based on Supreme Court’s legal theory, such theory not being repealeddue to possible lack of constitutionality. Notwithstanding its minor application,such position prevents the insurer from acting as a party in the procedure; neither toquestion the claim brought up by the acting party, nor even make appropriate use ofthe legal defense mechanisms to avoid condemnation. Specific restrictions to itsdefending rights are based on the article 764.3 of the «Ley de Enjuiciamiento Criminal», currently in force.We consider such interpretation as incompatible with the Fifth Directive andalso inapplicable to actual state of affairs.
Keywords: Primary liability insurance; Criminal procedure and capacity to be made a defendant.